An Analysis On Task of Reading Text in the TextbookEntitled Developing English Competencies Used By the Tenth Grade of SMA Negeri 1 Boyolali - Fauzia, Niar, Drs. Djoko Srijono, M.Hum, Dr. Dwi Haryanti, M.Hum (2015)
This research is to clarify the types of the reading task found in the textbook "Developing English Competencies" and to describe whether the indicator of reading task is compatible with the requirements of the indicators in the syllabus on the 2013 Curriculum. The results of the research are 1) the types of reading task are the open ended question type is 13 data or 39.39 %, multiple choice type is 3 data or 9.09 %, the vocabulary in a text type is 6 data or 18.18 %, the missing sentence is 2 data or 6.06 %, the writer opinion or reader response is 3 data or 9.09 %, putting the paragraph into the correct order is 2 data or 6.06 %, true/false reading task is 3 data or 9.09%, and matching the heading with the paragraph is 1 data or 3.03%. The open ended question is the most dominant type of all reading tasks that is in the textbook. 2) The compatibility of reading task between the textbook "Developing English Competencies" and the requirement of the syllabus on the 2013 Curriculum is 100% or in very good quality criteria. It means that the reading task on the textbook can be used by the students in tenth level of Senior High School.